Humor Translation Accuracy in Indonesian Subtitle of Kung-Fu School Movie - Joice Yulinda Luke (Ma Chung Press, 2022)
This study focused on investigating the accuracy of the translation of humour in Indonesian subtitle from Kung-Fu School movie. The aims of this research were: 1) to identify the types of humour in KungFu School movie, 2) to identify the strategy for translating humour into Indonesian movie subtitle, and 3) to analyse the accuracy of the humour translation in Indonesian subtitle of Kung-Fu School movie. The source of data was Kung Fu School movie downloaded from YouTube and the data were gathered from Indonesian subtitle as the target text. The analysis of data employed text-analysis using Spanakaki (2007) humour typology, Goettlieb (2001) translation strategy classification, and Nababan (2004) translation accuracy assessment rubric. The study indicates that fifty percent of humour types found in Kung-Fu School movie was Verbal Irony. In addition, the most strategy performed to translate humour into Indonesian subtitle were transfer with fifty two percent occurrences and then followed by other translation strategies such as Imitation, Condensation, and Paraphrasing that occurred in twelve percent in each. By contrast, Expansion and Dislocation were less applied or only eight percent and four percent compared to other translation strategies. At last, the results of study described only seventy percent of the humour translation found in Indonesian subtitle were accurate because of word-choices errors and grammatical mistakes.